Complex Repair of Anomalous Left Coronary Artery From the Pulmonary Artery in a 55-Year-Old Patient. Issue 3 (May 2023) - Lee, Timothy; Cohen, Jennifer L.; Chan, Alice; Zaidi, Ali N.; Boateng, Percy; Murthy, Raghav A.
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a congenital malformation that classically presents within the first year of life. Few patients survive into adulthood, and initial presentation after the fourth decade of life is rare. We describe a 55-year-old woman who presented after cardiac arrest. She initially refused surgery and underwent automated implantable cardioverter defibrillator placement, followed later by surgical repair involving reimplantation of the left coronary artery to the aorta and pulmonary artery reconstruction using interposition grafts. We report this late presentation of ALCAPA and successful surgical management.